2011
DOI: 10.1021/la104350g
|View full text |Cite
|
Sign up to set email alerts
|

Micellization and Phase Separation for Triblock Copolymer 17R4 in H2O and in D2O

Abstract: The reverse Pluronic triblock copolymer 17R4 is formed from poly(propylene oxide) (PPO) and poly(ethylene oxide) (PEO): PPO(14)-PEO(24)-PPO(14), where the subscripts denote the number of monomers in each block. In water, 17R4 shows both a transition to aggregated micellar species at lower temperatures and a separation into copolymer-rich and copolymer-poor liquid phases at higher temperatures. For 17R4 in H(2)O and in D(2)O, we have determined (1) the phase boundaries corresponding to the micellization line, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 41 publications
6
34
1
Order By: Relevance
“…2(c) and 2(d) respectively. It was established that ∆H and CMT are significantly affected by replacing H2O by D2O [62,63]. However, in the present case, no significant change was observed on the CMTs of both the copolymers by replacing water with D2O.…”
Section: Insert Fig2contrasting
confidence: 50%
“…2(c) and 2(d) respectively. It was established that ∆H and CMT are significantly affected by replacing H2O by D2O [62,63]. However, in the present case, no significant change was observed on the CMTs of both the copolymers by replacing water with D2O.…”
Section: Insert Fig2contrasting
confidence: 50%
“…While we did not deliberately investigate the formation of the film when samples were in regions II and III, we never observed the film except in region I. This surface film has not been studied in 17R4 in H 2 O [1]. Zhou and Chu [2] reported cloudiness in 17R4/H 2 O and found that it was eliminated by filtering the samples.…”
Section: Surface Layer Formation In Region Imentioning
confidence: 86%
“…Thus the end blocks are hydrophobic and the center block is hydrophilic, allowing for possibilities of self-assembly in water. The phase diagrams of 17R4 in H 2 O and in D 2 O [1,2] show micellization lines intersecting liquid-liquid phase separations with lower critical solution points. In Fig.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations